2017
DOI: 10.1080/10790268.2017.1383709
|View full text |Cite
|
Sign up to set email alerts
|

The effect of level of injury and physical activity on heart rate variability following spinal cord injury

Abstract: In this cohort of subjects spectral parameters of HRV were associated with the level of the injury. Passive standing was associated with higher HRV values in subjects with paraplegia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
0
10
1
1
Order By: Relevance
“…The present pilot study found that comprehensive evaluation of HRV and vascular age indicators addresses the full spectrum of poor AE, SDNN, and RMSSD in those with SCI. Studies have shown that physical activity, painting, respiratory training, music therapy, and nature therapy have the potential to reduce stress and improve HRV-related disorders and blood vessel structure[ 28 , 31 - 34 ]. Changes in the autonomic system, for example, are readily observed in response to physical exercise in individuals with SCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present pilot study found that comprehensive evaluation of HRV and vascular age indicators addresses the full spectrum of poor AE, SDNN, and RMSSD in those with SCI. Studies have shown that physical activity, painting, respiratory training, music therapy, and nature therapy have the potential to reduce stress and improve HRV-related disorders and blood vessel structure[ 28 , 31 - 34 ]. Changes in the autonomic system, for example, are readily observed in response to physical exercise in individuals with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Adjustments occur in the cardiac autonomic system as a result of exercise-induced remodeling of damaged axons, which increases sympathetic activity and may help to minimize risk of arrhythmia or sudden cardiac death in those with cervical SCI[ 28 ]. Kyriakides et al [ 31 ] examined the effects of regular physical workouts (four-hour sessions once a week for three months) on reducing the HRV of people with SCI, reporting that all HRV metrics improved in SCI patients who engaged in this exercise program. Other interventions have applied various relaxation techniques to reduce HRV.…”
Section: Discussionmentioning
confidence: 99%
“…Altered HRV is likely multifactorial, as HRV is influenced by various cardiovascular medications, 4 , 64 cardiac conditions, 8 , 27 , 32 neurological conditions, 1 , 12 , 35 anesthetics, 25 , 47 analgesia, 23 and pain. 10 , 24 , 31 , 33 , 44 , 46 , 60 , 62 This review provides some evidence that postsurgical pain itself may alter HRV.…”
Section: Discussionmentioning
confidence: 99%
“…Unopposed vagal influence on the cardiac SA and AV nodes results in neurogenic bradycardia and risk of AV block; even under maximal exercise influence, peak heart rates seldom exceed 120 beats per minute (bpm). Heart rate variability (HRV) has been assessed with spectral analysis in cervical and high thoracic SCI demonstrating parasympathetic dominance with increased high frequency (HF) domains; variable low frequency (LF) domains may reflect sympathetic or a combination of sympathetic and parasympathetic activity [ 8 , 9 , 10 , 11 ]. While HRV may provide some indication of relative SNS:PNS activity following acute SCI [ 11 ], it has proven to be a less reliable indicator in chronic SCI and warrants further investigation [ 9 ].…”
Section: Sci Influence On Ans Dysfunctionmentioning
confidence: 99%